AN INVESTIGATION AND ANALYSIS OF THE STEERING SYSTEM WITH THEIR CAPABALITIES - M. Kumaresan, K.Dinesh Kumar, J.Dhanapal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Steering system provides the directional change in the movement of an automobile and maintain in a position as per the driver’s decision without much strain on him. This system converts rotary movement of the steering wheel into angular movement of the front wheels. It multiplies driver’s effort by mechanical advantage, enabling him to turn the wheels easily.The steering system is a group of parts that transmit the movement of the steering wheel to the front and sometimes the rear wheels. The primary purpose of the steering system is to allow the driver to guide the vehicle.